Effectiveness of immune checkpoint inhibitor therapy on bone metastases in non-small-cell lung cancer - Abbott, Annalise G.; Meyers, Daniel E.; Elmi-Assadzadeh, Golpira; Stukalin, Igor; Marro, Alessandro; Puloski, Shannon K. T.; Morris, Don G.; Cheung, Winson Y.; Monument, Michael J. (Frontiers in Immunology, 2024)
Background: Bone metastases (BoMs) are prevalent in patients with metastatic non-small-cell lung cancer (NSCLC) however, there are limited data detailing how BoMs respond to immune checkpoint inhibitors (ICIs). The purpose of this study was to compare the imaging response to ICIs of BoMs against visceral metastases and to evaluate the effect of BoMs on survival.A retrospective, multicenter cohort study was conducted in patients with NSCLC treated with nivolumab or pembrolizumab in Alberta, Canada from 2015 to 2020.The primary endpoint was the real-world organ specific progression free survival (osPFS) of bone versus visceral metastases. Visceral metastases were categorized as adrenal, brain, liver, lung, lymph node, or other intra-abdominal lesions. The secondary outcome was overall survival (OS) amongst patients with and without BoMs.Results: A total of 573 patients were included of which all patients had visceral metastases and 243 patients (42.4%) had BoMs. High PD-L1 expression was identified in 268 patients (46.8%).No significant difference in osPFS was observed between bone, liver, and intra-abdominal metastases (p=0.20 and p=0.76, respectively), with all showing shorter osPFS than other disease sites. There was no difference in the osPFS of extra-thoracic sites of disease in patients with high PD-L1 expression. There was significant discordance between visceral disease response and bone disease response to ICI (p=0.047). The presence of BoMs was an independent poor prognostic factor for OS (HR 1.26, 95%CI: 1.05-1.53, p=0.01) Conclusion: Metastatic bone, liver, and intra-abdominal lesions demonstrated inferior clinical responses to ICI relative to other sites of disease. Additionally, the presence of bone and liver metastases were independent poor prognostic factors for overall survival. This real-world data suggests that BoMs respond poorly to ICI and may require treatment adjuncts for disease control.